2018
DOI: 10.1002/cssc.201701841
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Polyols with Trimethylphosphate in the Presence of a Lewis or Brønsted Acid Catalyst

Abstract: The alkylation of alcohols and polyols has been investigated with alkylphosphates in the presence of a Lewis or Brønsted acid catalyst. The permethylation of polyols was developed under solvent-free conditions at 100 °C with either iron triflate or Aquivion PW98, affording the isolated products in yields between 52 and 95 %. The methodology was also adjusted to carry out peralkylation with longer alkyl chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Al-OH groups can potentially be methylated by TMP, but this involves the use of strong Brønsted (sulfuric or trifluoro-methanesulfonic acid) or Lewis acids (transition metals or lanthanide triflates) as a catalyst. 27 Their methylation under neutral conditions has also been reported, but only at high temperature (T > 160°C) and for extended reaction times. 38 In our case, the use of relatively low temperature (120°C) and short reaction time (1 h) prevents the reaction of most of the (Fig.…”
Section: Insights Into the Reaction Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Al-OH groups can potentially be methylated by TMP, but this involves the use of strong Brønsted (sulfuric or trifluoro-methanesulfonic acid) or Lewis acids (transition metals or lanthanide triflates) as a catalyst. 27 Their methylation under neutral conditions has also been reported, but only at high temperature (T > 160°C) and for extended reaction times. 38 In our case, the use of relatively low temperature (120°C) and short reaction time (1 h) prevents the reaction of most of the (Fig.…”
Section: Insights Into the Reaction Mechanismmentioning
confidence: 99%
“…of alkyl phosphate. 27 They proposed a reaction mechanism under acid catalysis that leads to the formation of a dialkyl phosphate, and further showed that the dialkyl phosphate is unable to alkylate aliphatic alcohols.…”
Section: Insights Into the Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Diglycerolbased surfactants can be also produced such as diglycerol esters, 23 acetals, 24 and ethers. 18 Other ether derivatives can be also prepared by dehydrogenative arylation 25 or permethylation 26 to give hydrotropes and solvents, respectively. The selective oxidation of polyols, especially those incorporating a 1,2-diol motif, provides -hydroxyketones, that are encountered in natural products and serve as useful synthetic intermediates.…”
Section: Selective Catalytic Oxidation Of Diglycerolmentioning
confidence: 99%
“…In recent years, methylation methods were developed with greener agents, such as CO 2 , formic acid or dimethyl carbonate . Other alternative reagents such as dimethyl sulfite and trimethylphosphate were also proposed by our group. The borrowing hydrogen methodology allows the use of alcohols as alkylating agents through an aldehyde intermediate, generating water as the sole by‐product .…”
Section: Introductionmentioning
confidence: 99%